Strengthening Model Based on Responsibility to the Election Supervisory Body's Authority in Handling Money Politics to Realize Elections with Integrity - Isharyanto, Isharyanto; Madalina, Maria (Law Research Review Quarterly, 2018)
This research formulates a reinforcement model based on responsibility towards the authority of the Election Supervisory Board (Bawaslu) in handling money politics. The formulation of this model is important for realizing elections with integrity. Based on the strengthening of Bawaslu through legislative reforms, there is hope for the prevention of money politics in legislative elections, because the body carries out prevention and enforcement with the authority to decide upon disputes in the electoral process and administrative violations, as well as institutionally to exercise such authority, to be strengthened by the strengthening of Election Supervisors at the level of the Election Regency / City becomes Regency / City Bawaslu. By using an understanding of organizational behavior, the reinforcement model based on responsibility will rely on interpersonal relationships, information transfer, and decision making.